The Effect of Training and Placement Through Motivation on Employee Performance at Bank Jambi Muara Bulian Branch Office - Fitriadi Darussalam; M. Zahari; Osrita Hapsara (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
Improving the quality of human resources through appropriate training and placement of employees according to competencies can boost work motivation and ultimately improve employee performance. This research was conducted at Bank Jambi's Muara Bulian Branch Office. The aim was to analyze the effect of training and placement on employee performance, with work motivation as a mediating variable. The population in this study was all 84 employees of Bank Jambi's Muara Bulian Branch Office. Given the relatively small population, the sampling technique used was a census, with the entire population as respondents. The research method used was quantitative with a descriptive and verification approach. Data collection was conducted using a Likert-scale questionnaire, while data analysis used path analysis to test the direct and indirect effects between variables. The results showed that training and placement had a positive and significant effect on work motivation. Furthermore, work motivation had a positive and significant effect on employee performance. Training and placement also had a positive and significant effect on employee performance, both directly and indirectly through work motivation. Thus, work motivation was proven to act as a mediating variable in the relationship between training and placement on employee performance. These findings indicate that improving the quality of training and accurate employee placement requires management's attention in efforts to sustainably improve employee performance.